PERAN SEMANTIS PARTIKEL KASUS NI (に), GA (が), DAN O (を) SEBAGAI PENANDA OBJEK (Kajian Struktur dan Makna) - Lina Rosliana (IZUMI, 2013)
ABSTRACT Particle is a part of speech which has no conjugation and always stand with another part of speech in a clause or sentence. In Japanese language, particle is divided into three numbers of groups. There are, Case Particle (kakujoshi), Conjunction Particle (setsuzokujoshi), and Final Sentence Particle (shuujoshi). Case particle consist of ni, ga, o, he, de, to, kara, made, and yori. Those are particles that take position after noun or noun phrase which stands in function of subject or object. They represent semantic role of word they stick with. Keywords: Japanese language, particle, case particle, object, semantic role